2019
DOI: 10.1177/1362361319830029
|View full text |Cite
|
Sign up to set email alerts
|

‘I definitely feel more in control of my life’: The perspectives of young autistic people and their parents on emerging adulthood

Abstract: Long-term outcomes studies often paint a discouraging picture of the lives lived by autistic adults. Yet, their outcomes are often measured against normative markers of traditional adult roles, which may not apply to autistic people making the transition to adulthood. Here, we investigated the transition experiences of a group of young autistic people who were followed from childhood. Twenty-six young people and their parents ( n = 28) participated in semistructured interviews on the process of transition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
65
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 77 publications
7
65
0
1
Order By: Relevance
“…To close the gap between what individuals with ASD and their families want for their future (Chen et al, 2019; Cribb et al, 2019) and what is actually happening (Shattuck et al, 2012), interventions that support functional independence are needed. The combination of two evidence-based practices—work systems and parent-implemented interventions—show promise to enhance independent initiation and completion of daily living tasks, and thus have potential to contribute to closing that gap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To close the gap between what individuals with ASD and their families want for their future (Chen et al, 2019; Cribb et al, 2019) and what is actually happening (Shattuck et al, 2012), interventions that support functional independence are needed. The combination of two evidence-based practices—work systems and parent-implemented interventions—show promise to enhance independent initiation and completion of daily living tasks, and thus have potential to contribute to closing that gap.…”
Section: Discussionmentioning
confidence: 99%
“…Parents have noted concern because they either support their child in doing daily tasks (e.g., cooking, cleaning) and self-care, or supervise their child engaging in the tasks (Sosnowy et al, 2018). Parents have identified difficulties with initiation as well as with self-regulation and executive functioning skills as a challenge to their child's transition to becoming independent (Cribb et al, 2019). Independence is often listed as a challenge for individuals on the autism spectrum, especially as they age and expectations for independence increase into adulthood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a qualitative study identified a group of young people with ASD seen in childhood and interviewed them 12 years later. 22 The thematic analysis identified that the young people (at age 16-20 years) felt more in control of their own lives, needed to take one step at a time and valued their 'social connections with others'. Both these studies highlight the importance of the wider context for the young person, and that acknowledging the young people's need for more time to take on young adult roles and responsibilities, is likely to promote well-being and a sense of self-identity.…”
Section: Transition Contextsmentioning
confidence: 99%
“…26 27 There is a limited understanding, however, of what a 'good life' means to autistic people and which factors play a critical role in helping them to participate in education, employment and community life, in the ways that matter most to them. 28 These factors, for the most part, have remained elusive, especially for those individuals without an additional intellectual disability. 27 29 Listening to, and learning from, the life histories of those who went through childhood without a diagnosis could serve better to inform diagnostic practices and ways of improving the lives of autistic people, though identification of risk and resilience factors and appropriate support.…”
Section: Introductionmentioning
confidence: 99%